2012
DOI: 10.1016/s0140-6736(12)61082-4
|View full text |Cite
|
Sign up to set email alerts
|

Routine versus clinically indicated replacement of peripheral intravenous catheters: a randomised controlled equivalence trial

Abstract: Australian National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
306
8
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 364 publications
(365 citation statements)
references
References 36 publications
22
306
8
17
Order By: Relevance
“…In a multicentre, non blinded, randomized controlled equivalence trial Rickard and colleagues [6] investigate the safety, effectiveness and possible benefits of clinically indicated replacement of IVC as compared to routine replacement. Patients were considered eligible if they were at least 18 years old and they were scheduled or expected to have a peripheral IVC in situ for 4 days or more.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicentre, non blinded, randomized controlled equivalence trial Rickard and colleagues [6] investigate the safety, effectiveness and possible benefits of clinically indicated replacement of IVC as compared to routine replacement. Patients were considered eligible if they were at least 18 years old and they were scheduled or expected to have a peripheral IVC in situ for 4 days or more.…”
Section: Discussionmentioning
confidence: 99%
“…Se consideró este criterio si había registro en relación a las condiciones del CVP dentro de las 12 hrs previas al estudio, donde al menos se debía mencionar la existencia del CVP. La permanencia del CVP fue evaluada pero no fue incluida como criterio de seguridad [4][5][6][7] .…”
Section: Artículo Originalunclassified
“…Para aportar en el conocimiento del manejo de los CVP en nuestro medio, se efectuó una evaluación de las condiciones de seguridad de estos dispositivos en pacientes adultos en un hospital general. Sus resultados permiten poner en perspectiva posibles cambios en las recomendaciones sobre la duración de los CVP que han surgido recientemente en la literatura médica [4][5][6][7] .…”
Section: Introductionunclassified
“…Since the CI lied between -3 % and ?3 % (the pre-specified equivalence margin) (Fig. 3), the authors concluded that the two treatments were equivalent [1].…”
mentioning
confidence: 99%
“…The trial by Rickard and colleagues [1] was designed to assess the incidence of phlebitis in a group of patients who had intravenous catheters replaced when clinically indicated in comparison with a group of patients with catheters removed every third day. The aim of the study was not to demonstrate that one of the two strategies was better than the other, but that patients who had intravenous catheters replaced when clinically indicated would have equivalent rates of phlebitis, and no difference in other complications, but reduced costs and number of catheter insertions, compared with patients with catheters removed every third day.…”
mentioning
confidence: 99%